Activity Analysis, Semantics and Metadata Building. Issue 2 (2nd April 2016) - Cote, Christian
Abstract : We propose a methodology for building consistent metadata for the description of scientific working documents. Our methodology is supported by distributed cognitive theoretical principles and implemented through a combination of anthropological, semantic, and linguistic approaches. Our analysis is applied to a particular pharmacist activity—namely, the adaptation of posology. Issues focus on the representation of situations that describe individuals, tools, and artifacts. Regular relations between these situations characterize types that allow the description of conceptual contents associated with these empirical objects. Because these situations and types are expressed by a set of metadata and then associated with current metadata, our proposal extends the nature of entities described by metadata to useful internal activity artifacts.